2019
DOI: 10.7759/cureus.4035
|View full text |Cite
|
Sign up to set email alerts
|

Morgagni-Larrey Hernia: A Possible Cause of Recurrent Lower Respiratory Tract Infections

Abstract: Morgagni-Larrey hernia is an exceedingly rare presentation of congenital diaphragmatic hernia. Despite its rarity, it is associated with significant risk of morbidity and mortality. Herein, we describe a unique case report of an elderly woman who presented with left-sided chest pain, dyspnea, and chronic history of recurrent respiratory tract infections. On the basis of her medical history, general physical examination and imaging studies, she was operated for a presumptive diagnosis of thymolipoma. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Imaoka et al [ 28 ] Temp ≥ 37.4 °C (1) 1/3 84.9% (77.4–94.5%) 68.6% (63.7–73.6%) 0.800 (0.745–0.854) CRP ≥ 4.7 (1) Periappendiceal fluid Yes (1) 3. Khan et al [ 16 ] Age 40–59 years (1) 2/4 73.4% (62.6–84.3%) 58.8% (53.6–61.1%) 0.694 (0.630–0.759) ≥ 60 years (2) Duration of symptoms ≥ 2 days (1) Appendicolith Yes (1) 4. TH Kim et al [ 33 ] Appendiceal diameter > 10 mm (1) 3/4 56.3% (44.1–68.4%) 86.1% (82.4–89.8%) 0.777 (0.718–0.835) Ascites Yes (1) Fat stranding Yes (1) CRP > 5.0 mg/dL (1) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Imaoka et al [ 28 ] Temp ≥ 37.4 °C (1) 1/3 84.9% (77.4–94.5%) 68.6% (63.7–73.6%) 0.800 (0.745–0.854) CRP ≥ 4.7 (1) Periappendiceal fluid Yes (1) 3. Khan et al [ 16 ] Age 40–59 years (1) 2/4 73.4% (62.6–84.3%) 58.8% (53.6–61.1%) 0.694 (0.630–0.759) ≥ 60 years (2) Duration of symptoms ≥ 2 days (1) Appendicolith Yes (1) 4. TH Kim et al [ 33 ] Appendiceal diameter > 10 mm (1) 3/4 56.3% (44.1–68.4%) 86.1% (82.4–89.8%) 0.777 (0.718–0.835) Ascites Yes (1) Fat stranding Yes (1) CRP > 5.0 mg/dL (1) …”
Section: Resultsmentioning
confidence: 99%
“…We revised the cutoff of the CRP level to ≥ 3 mg/dL because a CRP level of 0–3 mg/dL is used as the reference limit in our and most other hospital laboratories. Furthermore, Khan et al [ 16 ] used two continuous variables, namely age and abdominal pain duration, and one discrete variable, namely appendicolith (present or absent), in their model. We used the cutoff values of 40 and 60 years for age and ≥ 2 days for the abdominal pain duration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted with 4872 participants above the age of 18 in Wuhan, it was found that the rate of depression was 48.3%, the rate of anxiety was 22.6%, the rate of depression and anxiety was 19.4% during the COVID-19 outbreak [ 54 ]. In studies conducted with patients with diabetes, it was found that anxiety and depression were observed at a high rate during the COVID-19 pandemic [ 55 , 56 ]. Similar to the literature, in this study, anxiety, and depression symptoms were observed with a high rate in participants.…”
Section: Discussionmentioning
confidence: 99%